Passive Ozone Sampling in Jundiaí, São Paulo, Brazil (Sustainability in Debate, 2015)
In Jundiaí city, in the Brazilian State of Sao Paulo, ozone sampling began in 1990 and was implanted by the Environmental Company of the State of São Paulo ”“ CETESB. In 2008, CETESB started the annual automatic ozone monitoring in Jundiaí city. Since then, increasing ozone concentrations have been detected and the standard of air quality has proven to be frequently exceeded. This article is the result of a study on the distribution of the pollutant in three different areas in order to evaluate and understand pollutant behaviors in the city. Passive collectors Ogawa® containing filters were used and subsequently analyzed in Ionic Chromatography. A statistical study of the results was performed through an Analysis of Variance (ANOVA) method with a 95% confidence interval. Results of the sampling campaign demonstrated a higher concentration of the pollutant in urban regions with a presence of natural vegetation and of plantations. However, air quality standards were not exceeded and statistical analyses showed no significant differences among these results.